STRATEGI PENGAWAS SEKOLAH DASAR DALAM MELAKSANAKAN PENGAWASAN KE SEKOLAH BINAAN - Teti Berliani; Rina Wahyuni; Elga M. Helencia; Andreini Maretin; Siono M. Putra (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2022)
The purpose of this research is to analyze and describe the strategy of primary school supervisors in carrying out supervision of the target schools in the City of Palangka Raya, which focuses on: (1) the mechanism of supervision by school supervisors in the target schools; and (2) the obstacles faced by school supervisors in carrying out supervision in the target schools. The approach used is qualitative with a case study design. Data was collected by observation, interviews and documentation. Data analysis was carried out by adopting an interactive pattern from Miles et al (2014). The results showed that the primary school supervisor's strategy in carrying out the supervision of the target schools had been going well and regularly scheduled so that it had a positive impact both for teachers and principals in particular and for schools in general.